INTER-UNIVERSITY COOPERATION BETWEEN FRANCE AND BOSNIA AND HERZEGOVINA - STUDENT MOBILITY AND THE ROLE OF THE FRENCH EDUCATION SYSTEM IN STRENGTHENING HIGHER EDUCATION IN BOSNIA AND HERGOVINA - Perišić, Nikola (Serbian political thought, 2023)
Higher education plays a key role in the development of a country and society. Cooperation between different universities and educational institutions at the international level plays a crucial role in enriching the educational experience of students, exchanging knowledge and innovation, and promoting cultural diversity. The paper shows how the French model of education has an impact on the development of higher education in Bosnia and Herzegovina. The specificity of Bosnia and Herzegovina is reflected in the multiculturalism that dominates that country, but also in the fact that this country has been constituting as a state for the last few decades. Because of all this, and in order to represent the interests of different groups in the most successful ways, Bosnia and Herzegovina applied existing successful models in various social spheres, including in education. The French model of education, which represents one of the world's most successful models in higher education, was one of the most dominant educational models in Bosnia and Herzegovina. In addition, the French state, through various incentives such as donations or scholarships to the best students, influenced the development and institutionalization of universities throughout Bosnia and Herzegovina, and currently there are eight state universities in that area. The basic hypothesis on which the work is based is that the application of the French educational model in Bosnia and Herzegovina contributes to the improvement of the quality of higher education, especially in terms of academic excellence and research capacities. The method based on which the hypothesis is tested is the method of technology and knowledge transfer techniques, and as an additional method, the comparative method will be used.
Keywords: : higher education, inter-university cooperation, Bosnia and Herzegovina, transfer of technology and knowledge and student mobility.